DESKTOP-BASED PLANTATION MONITORING INFORMATION SYSTEM DESIGN - Valian Yoga Pudya Ardhana; M. Dermawan Mulyodiputro (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2022)
Lombok Island has extensive land resources with a lot of water content so that it is suitable to be managed and utilized for plantation. The Local Government continues to try to expand the planting area of ​​the plantation sector in order to increase production. To control management and development in plantation sector, Local Government needs a plantation monitoring information system. Some aspects of plantation that can be monitored include the location and area of ​​planting, types of plantation commodities, number of trees, amount of production, planting time, estimated harvest time, income and outlay. With the monitoring system, complete plantation data will be obtained so that Local Government can establish appropriate policies to increase production yields in plantation sector. The plantation monitoring information system designed is desktop-based. The results obtained from the design are MySQL database design and User Interface design.Desktop-Based, Plantation, Monitoring, Information System, Design